No-lose method – Thomas Gordon’s conflict-resolution method in practice - Sipos, Margit Erika (Autonomy and Responsibility Journal of Educational Sciences, 2022)
After a short summary of Gordon’s six steps no-lose method I wil present an opportunity of implementation in practice. How can we implement in pedagogical context of a dormitory this common practical model of humanistic psychology and pragmatic philosophy which was described and presented in Gordon’s books, among others?